Impact of system-level activities and reporting design on the number of incident reports for patient safety. Issue 2 (29th March 2010) - Fukuda, H; Imanaka, Y; Hirose, M; Hayashida, K
Abstract : Background: Incident reporting is a promising tool to enhance patient safety, but few empirical studies have been conducted to identify factors that increase the number of incident reports. Objective: To evaluate how the number of incident reports are related to system-level activities and reporting design. Methods: A questionnaire survey was administered to all 1039 teaching hospitals in Japan. Items on the survey included number of reported incidents; reporting design of incidents; and status for system-level activities, including assignment of safety managers, conferences, ward rounds by peers, and staff education. Staff education encompasses many aspects of patient safety and is not limited to incident reporting. Poisson regression models were used to determine whether these activities and design of reporting method increase incident reports filed by physicians and nurses. Results: Educational activities were significantly associated with reporting by physicians (53% increase, p<0.001) but had no significant effect on nurse-generated reports. More reports were submitted by physicians and nurses in hospitals where time involved with filing a report was short (p<0.05). The impact of online reporting was limited to a 26% increase in physicians' reports (p<0.05). Conclusion: In accordance with the suggestions by previous studies that examined staff perceptions and attitudes, this study empirically demonstrated that to decrease burden to reporting and to implement staff educations may improve incident reporting.